THE USE OF REMOTE SENSING DATA IN SELECTING SITES FOR THE ESTABLISHMENT OF GREEN SPACES IN THE CITY OF MOSUL - Basman Younis Hameed (Mesopotamia Journal of Agriculture)
The aim of this study is to select different sites to increase the forestry regions and green spaces around and inside Mosul city to protect the risky environmental condition that happens due to the shortage and shrinkages of green areas and high temperatures, gasses emission affects human health because of the settlement of environmental pollutants in the city which is facing to a numbers of cyclone during latest years due to the drought phenomenon cover most of agricultural areas. Natural factors such as geomorphology, land use/ land cover, drainage system, soil and climate conditions have been studied and five sites have been chosen; these sites comprises: Tigris river flood plain, intermittent and perennial tributaries and others in the NW and south of the city for stabilization forestry regions and green spaces around the city. The study was also including the species of trees that are suitable to the conditions of each site selected and the climate of the city.